In vitro and in vivo studies on the potential effects of Melaleuca cajuputi and Ardisia elliptica on lymphatic filariasis : A strategy targeting the Wolbachia / Nazeh Mohammed Al-Abd Ali - Nazeh Mohammed, Al-Abd Ali (2016)
Lymphatic filariasis (LF) is caused by parasitic filarial nematodes. Currently available therapeutics are largely effective against the microfilaria stage, and they have a limited influence on the adult worms that are actually causing the disease. The present study aims to investigate the knowledge, attitudes, and practice with regards to LF among the population of an endemic area in Terengganu, Malaysia, and to explore the antifilarial activity of local medicinal plant extracts. In vitro antioxidant, antibacterial, and antifilarial activity tests were performed to assess the potential activities of these extracts. In order to develop and study the infection in vitro, Mongolian gerbils were infected intraperitoneally with B. pahangi larvae (L3) and they were used to host adult worms. The potential anti-filarial activities of the plant extracts of Melaleuca cajuputi and Ardisia elliptica were evaluated in vitro using methyl-thiazolyl-tetrazolium (MTT) assays, electron microscopy, and polymerase chain reaction (PCR). The extracts were fractionated using high-performance liquid chromatography (HPLC). The effect of each fraction was tested against Wolbachia in vitro using Aedes albopictus cells line (Aa23) cells. The active fractions were further subjected to liquid chromatography-mass spectrometry (LC-MS) to identify the active ingredients. The toxicities of the active extracts and isolated compounds were investigated. The identified compounds were then tested in vitro and in vivo, against adult worms and Wolbachia. RT-PCR was used to measure the expression levels of the Wolbachia surface protein (wsp) and Filamenting temperature-sensitive mutant Z (Fstz) and the B. pahangi genes. Baseline results have demonstrated that more than 80% of the respondents have become cognizant of LF, and additionally 70% of these individuals have grasped the fact that the LF is not devoid of problems. Estimatedly, 77% indicated that filariasis was transmitted by mosquitoes. Only 35% of the participants in this research were well aware of the local Mass Drug Administration (MDA) program held in the area. All plant extracts showed good antioxidant activity, free radicals scavenging and antibacterial activity. A methanolic extract of M. cajuputi flowers significantly reduced adult worms’ viability and release of microfilariae. Caffeic acid phenyl ether (CAPE) was identified as the active constituent in M. cajuputi. It showed significant micro and macrofilaricidal activities in vitro and in vivo. In summary, it has been discovered in this study that most respondents did acknowledge LF, in spite of the fact that their knowledge of MDA was rather limited. There is a need to enhance the delivery of health education and information programs, as well as mass mobilization campaigns, in order to improve understanding of the LF in the affected population for the control program to be successful. In the present study, the methanol extract of M. cajuputi flowers, and CAPE possesed anti-filaricidal activites. The mechanism of action of the CAPE is suggested to be due to its anti-Wolbachia activity; this compound has been shown to significantly downregulated the expression of the wsp, fstz, and Shp-1 genes. Therefore, CAPE could be a promising candidate drug for the treatment of LF.